2010
DOI: 10.1681/asn.2009060624
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Linkage and Association Scan in Primary, Nonsyndromic Vesicoureteric Reflux

Abstract: Primary vesicoureteric reflux accounts for approximately 10% of kidney failure requiring dialysis or transplantation, and sibling studies suggest a large genetic component. Here, we report a wholegenome linkage and association scan in primary, nonsyndromic vesicoureteric reflux and reflux nephropathy. We used linkage and family-based association approaches to analyze 320 white families (661 affected individuals, generally from families with two affected siblings) from two populations (United Kingdom and Sloven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 55 publications
0
78
0
10
Order By: Relevance
“…Three linkage studies, however, have been unable to support these findings. One study on Italian and American kinships with VUR, one on four Dutch families with VUR, and one on UK and Slovenian data sets with VUR found no linkage to the locus of ROBO2 (6,8,11). In this study, syndromic cases of VUR were excluded, and the cases of primary nonsyndromic VUR accompanied by RHD were studied separately.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Three linkage studies, however, have been unable to support these findings. One study on Italian and American kinships with VUR, one on four Dutch families with VUR, and one on UK and Slovenian data sets with VUR found no linkage to the locus of ROBO2 (6,8,11). In this study, syndromic cases of VUR were excluded, and the cases of primary nonsyndromic VUR accompanied by RHD were studied separately.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have identified variants of the roundabout, axon guidance receptor, homolog 2 (ROBO2) gene in patients with VUR and VUR accompanied by other CAKUT, but their conclusions are contradictory on whether or not mutations of the ROBO2 gene are a causative factor of VUR or VUR-other CAKUT (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…104 However, another study investigated the Gly691ser mutation in 221 unrelated index cases, 190 of their affected siblings and 592 controls from the irish population, and found no evidence of any influence of RET snP rs1799939 on vur phenotype, which is consistent with the absence of evidence for linkage of vur to RET observed by other studies. 24,105,106 roBo2/sliT2 to date, two groups have reported ROBO2 gene missense mutations associated with vur, 107,108 and a further study has supported the hypothesis that variations in ROBO2 and SLIT2 are rare causes of vur in humans. 109 However, subsequent candidate gene linkage studies including the ROBO2 locus found no evidence for linkage, 23 and similar study has found no evidence of linkage at SLIT2.…”
Section: Human Genetic Studiesmentioning
confidence: 91%
“…in addition, they tested for, but did not detect, associations with the major candidate genes AGTR2, HNF1B, PAX2, RET, ROBO2, and UPK3A. 105 Modest evidence for linkage to several regions (table 4) was found, particularly when the nonparametric analysis was restricted to cases with confirmed vur (rather than reflux nephropathy or other proxy phenotypes) and when parametric analysis allowed for the existence of multiple loci. the results provided some support for the regions identified on chromosomes 3, 6 and 21 by Kelly et al and on chromosome 1 by Conte et al in the family-based analysis, associations were found with one single nucleotide polymorphism (snP) in the uK families, three snPs in the slovenian families and three snPs in combined families.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation